Amphiphilic Cyclodextrin‐Based Nanoparticulate Vaccines Can Trigger T‐Cell Immune Responses. Issue 4 (29th December 2021) - Geisshüsler, Silvana; Schineis, Philipp; Langer, Lara; Wäckerle-Men, Ying; Leroux, Jean-Christophe; Halin, Cornelia; Vogel-Kindgen, Sarah; Johansen, Pål; Gander, Bruno
Abstract : Particulate antigen‐delivery systems are instrumental for therapeutic vaccination, aiming at improving the safety and efficacy of treatments by targeting specialized antigen‐presenting cells (APCs). However, the induction of potent adaptive immune responses, especially cellular immunity, remains a major challenge. Herein, a novel nanoparticulate antigen‐delivery system based on amphiphilic cyclodextrins (CDs) is developed as a platform for therapeutic cancer vaccination. Supramolecular nanosized CD structures are formed in aqueous media and loaded with peptide antigens. The nanoparticle's adjuvant capacity is tested in cell experiments with murine bone marrow‐derived dendritic cells (BMDCs) or macrophages and T cells. Peptide‐loaded nanoparticles cause upregulation of costimulatory molecules on BMDCs and facilitate activation and proliferation of antigen‐specific T‐lymphocytes in vitro. Correct processing for major histocompatibility complex (MHC) class‐I antigen presentation is demonstrated using a capped version of the ovalbumin‐derived peptide SIINFEKL (c‐SFL). After immunization of mice with peptide‐loaded CD nanoparticles, the frequencies of antigen‐specific and cytokine‐producing CD8 + T cells are increased. This work sheds light on the immune‐stimulating properties of amphiphilic CD nanoparticles and reveals their considerable potential as carriers for cancer vaccines. Abstract : Cyclodextrins are derivatized with alkyl chains to render them amphiphilic and formed into nanoparticles using a nanoprecipitation technique. Model peptides are successfully loaded and the NPs efficiently taken up by cells. The nanovaccines lead to upregulation of maturation markers as well as activation and proliferation of T cells. When immunizing mice with the vaccine, an adaptive immune response is elicited.